Research on the Dissemination and Influence of the English Translations of Journey to the West - Huang, Jialing (Transactions on Social Science, Education and Humanities Research, 2024)
The four great Chinese classics possess a high literary standard and profound thinking, representing four great monuments in the history of Chinese literature. Their translation and dissemination abroad are an important part of the national strategy of "Chinese culture going global", and are incorporated into the major policies of national cultural development. However, previous research on English translations has mostly focused on translation techniques, translator's motivation, comparisons with the original text, etc., with a lack of statistical, analytical, and research from the field of communication. Therefore, this project takes the 25 English translations of Wu Cheng'en's novel "Journey to the West" as the research subject, conducts statistical analysis on the reprinting of different translations, overseas reading volume and reader book reviews, magazine book reviews, academic citation times and world library collection quantities, examines the dissemination of different translations in the English-speaking world, and based on the current situation, combines contemporary scholars' views on the dissemination and translation research of "Journey to the West" in English, lays the foundation for proposing improvement strategies for the national "going global" policy, to promote the breadth and depth of Chinese culture's dissemination in the English-speaking world, supporting the spread of Chinese classical culture and thought beyond China's borders.